Detection of Programming Plagiarism in Computing Education: A Systematic Mapping Study - Gomes, Kaio Pablo; Matos, Simone Nasser (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2020: Anais do XXXI Simpósio Brasileiro de Informática na Educação, 2020)
The programming plagiarism is increasingly a problem in computing education, and the proposed solutions for this growing concern rely on automatic detectors. The usage of the automatic tools for this purpose can provide benefits in education for professors and instructors of programming assignments, besides, to avoid the lack of essential skills from the students since they compromise their programming logic by plagiarizing. This paper performs a systematic mapping study aligned with a snowballing technique to analyzes the existing solutions for this domain. As contributions, tendencies, as well as information analysis, are provided to guide new proposals of solutions.